PERSISTENT COLONIC SCHISTOSOMIASIS AMONG SYMPTOMATIC RURAL INHABITANTS IN THE EGYPTIAN NILE DELTA - Mohamed Emara; Mohamed Ahmed; Amr Elfer; Ayman El-Saka; Asem Elfert; Sherief Abd-Elsalam (Mediterranean Journal of Hematology and Infectious Diseases, 2021)
Background and Aims: Human schistosomiasisis one of the most important and unfortunately neglected tropical diseases. The aim of the current study was to investigate the prevalence and characterize colonic schistosomiasis, among symptomatizing rural inhabitants of the Middle Northern region of the Egyptian Nile delta.